Towards a tidal loading model for the Argentine-German Geodetic Observatory (La Plata) - Richter, Andreas (2017)
Fil: Richter, Andreas. Universidad Nacional de La Plata. Facultad de Ciencias Astronómicas y Geofísicas. Laboratorio MAGGIA; Argentina